(untitled) (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Objective: To determine the frequency of hypomagnesemia among patients presenting with migraine at a tertiary care hospital. Methods: This descriptive cross-sectional study was conducted at the Outpatient Department of Neurology, Nishtar Medical College/Hospital, Multan, Pakistan, from May 16, 2019, to November 16, 2019. A total of 151 adult patients aged 20–60 years diagnosed with migraine were enrolled using non-probability consecutive sampling. Venous blood samples were collected to measure serum magnesium levels. Hypomagnesemia was defined as serum magnesium <1.3 mEq/L. Results: Out of 151 patients, 71 (47%) were found to have hypomagnesemia. Female patients were more commonly affected, accounting for 62% of the hypomagnesemic cases. There was a statistically significant association between diabetes and hypomagnesemia (p=0.047). No significant associations were observed between hypomagnesemia and age, duration of migraine, obesity, or residential status. Conclusion: Nearly half of the migraine patients had hypomagnesemia, highlighting the need for routine screening of serum magnesium levels in migraineurs. Further interventional studies are needed to assess whether magnesium supplementation can reduce the frequency and severity of migraine attacks.